Impact of perceived performance appraisal effectiveness and career commitment on knowledge worker turnover intention: a study of private universities in Malaysia / Marina Mustapha - Mustapha, Marina (2020)
Excessive employee voluntary turnover has long being acknowledged as a silent threat to any organization. This turnover phenomenon has been among the highly pressing concerns for institutions of higher education in Malaysia, particularly, among the private universities’ faculties. In spite of the attentiveness and responsiveness of high rates of turnover around the globe, research on the area of turnover or turnover intention, as well as, perceived performance appraisal effectiveness has been limited. Previous studies have undertaken either few elements of perceived performance appraisal effectiveness or failed to examine the aspect of perceived performance appraisal effectiveness from the core perspective of psychology. Past studies have not assessed the scale and nature of association between these two variables. Thus, this study primarily aims at exploring the impact of relationship between perceived performance appraisal effectiveness and turnover intention. Since earlier studies have further implied that positive perception of employee performance appraisal effectiveness could lead to higher career commitment, which may then impose a negative influence on employee turnover behavioral intention, the present study had additionally considered the mediating role of career commitment on the relationship between perceived performance appraisal effectiveness and turnover intention. The study had specifically focused on seventeen Malaysian private universities where data was gathered through 500 questionnaire surveys and twelve interviews from academics as the knowledge workers working in the service industry. Conceptual framework was developed that consisted of diverse dimensions of performance appraisal, career commitment and turnover intention. A set of four hypotheses were developed that assessed whether there existed a positive or negative relationship between these three variables. For analysing the data, the study had utilised various numbers of statistical techniques such as exploratory factor analysis, confirmatory factor analysis and cross-case analysis. The study results had indicated that the research model developed was a good predictor of turnover intention and provided the general support for all the four hypotheses. The study found that there was a positive relationship between perceived effectiveness of performance appraisal and knowledge worker career commitment, while there were negative relationships between perceived performance appraisal effectiveness and turnover intention as well as between career commitment and turnover intention. The study also found that career commitment partially mediated the relationship between perceived performance appraisal effectiveness and knowledge worker turnover intention among academics in Malaysia. The empirical relationships between faculty perceived performance appraisal effectiveness, career commitment and turnover intention further proposed that it would be favorable and advantageous to the private university management to recuperate faculty turnover situation. Further discussions included the research contributions, limitations and implications.